2023
DOI: 10.3389/fimmu.2023.1161067
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted nature of IL-10: regulation, role in immunological homeostasis and its relevance to cancer, COVID-19 and post-COVID conditions

Valentina Carlini,
Douglas M. Noonan,
Eslam Abdalalem
et al.

Abstract: Interleukin-10 (IL-10) is a pleiotropic cytokine that has a fundamental role in modulating inflammation and in maintaining cell homeostasis. It primarily acts as an anti-inflammatory cytokine, protecting the body from an uncontrolled immune response, mostly through the Jak1/Tyk2 and STAT3 signaling pathway. On the other hand, IL-10 can also have immunostimulating functions under certain conditions. Given the pivotal role of IL-10 in immune modulation, this cytokine could have relevant implications in pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 302 publications
0
11
0
Order By: Relevance
“…IL-10 and melatonin are pleiotropic molecules that exert context-and cell-dependent stimulatory and/or inhibitory effects upon the immune system. 2,4,35,36 The crosstalk among these signals composes a network of interconnections that coordinate the trimming and intensity of several immunological processes in health, pathophysiological, and pathological conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 and melatonin are pleiotropic molecules that exert context-and cell-dependent stimulatory and/or inhibitory effects upon the immune system. 2,4,35,36 The crosstalk among these signals composes a network of interconnections that coordinate the trimming and intensity of several immunological processes in health, pathophysiological, and pathological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic complexity of the system allows independent local and systemic modulations of melatonin content and, therefore, efficient coordination of physiologic and pathophysiologic processes. IL‐10 and melatonin are pleiotropic molecules that exert context‐ and cell‐dependent stimulatory and/or inhibitory effects upon the immune system 2,4,35,36 . The crosstalk among these signals composes a network of interconnections that coordinate the trimming and intensity of several immunological processes in health, pathophysiological, and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL-10 in tumor pathogenesis is controversial, with some findings showing that IL-10 promotes tumor development, while the other results show that this cytokine inhibits tumor growth and metastasis [35] . In immunosuppressive TME IL-10, produced by cancer cells, MDSCs, TAMs, Treg cells, enhances tumor cell survival, proliferation and metastasis by the inhibition of NK and CTL cells.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have indicated, the upregulation of IL-17a could activate the expression of downstream cytokines related to inflammation, including IL-1, IL-6, IL-8, and IL-22, 49,50 whereas IL-10 played a crucial role in suppressing inflammation production. 51,52 These findings suggest that exposure to chlorfenapyr might exacerbate inflammation by enhancing the expression of the proinflammatory factor IL-17a and reducing the anti-inflammatory factor IL-10, leading to an increase in the expression of inflammatory factors IL-1β, IL-6, and IL-22, and ultimately resulting in the development of intestinal inflammation.…”
Section: Chlorfenapyr Induced Intestinal Inflammationmentioning
confidence: 95%